(3TQM ThGgO TQM bWQ GdfOis - (3GdMSjfj, GdCYQLj, GdaMGe, UGOb Hf Ydj Hf GdMSf Hf gGTe, J (B1204(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj QaY bOQ GdYdeGA Edi CSeG eMd(B... (3deG cGf cJGH (B... (3GHf gTGe GdCfUGQj GdeSei HbWQ GdfOi(B... (3YdbJ YdjgG TQMGs
(3BNQgG (B:s
(3dG jLhR GdENHGQ HGdeYQaI Yf GdfcQI hGdeUfa EfeG LQG Ydi ePgH SjHhjgs
(3JHUQI GdeDda (B:s
(3JGQjN haGJg aj HYV GdeUGOQ(B: 1205(3g`, hGSeg aj HYV GdeUGOQ(B: (3UGOb Hf eMeO Hf GdMSfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B3(3, U(B186s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B825s
(3GdCYdGe(B: (3L(B3(3, U(B186s
Keywords: (3GdfMhs